OS ESTÁGIOS OBRIGATÓRIOS DE UM CURSO DE PEDAGOGIA E A CONSTITUIÇÃO DA PRÁXIS PEDAGÓGICA DE PROFESSORES INICIANTES: possíveis relações - WEVERLIN FERREIRA BRIZOLA (2024)
In the initial training, the mandatory internship allows the insertion of future teachers in the reality of the institutions, especially the public ones and, even if in a minimized way, allows the graduate to become familiar with the daily school, representing, then, a moment of action between theory and practice. The objective of this master’s research was to analyze possible relationships between the proposals of compulsory internships of a Pedagogy course and the constitution of the pedagogical praxis of beginners teachers, graduates of the course. Thus, this dissertation has as object of study the constitution of pedagogical praxis in beginning teachers working in the public school system in the city of Campo Grande/ MS, who are graduates of the Pedagogy course of the School of Education (Faed) of the Federal University of Mato Grosso do Sul (UFMS). For this, we sought to establish relationships between the initial training and the constitution of pedagogical praxis, discuss the specificities of the mandatory internship in the initial training of Pedagogos For the constitution of pedagogical praxis from the analysis of narrative interviews of self formative character with five teachers graduates of the Pedagogy course of UFMS and who are active in public schools. The assumptions of the Biographical Method were used as a theoretical-methodological reference, which understands that the reports themselves, constitute research data that can contribute to the understanding of educational or social issues. Therefore, the narrative research, through the production of narrative interviews, makes it possible to understand how the pedagogical praxis was being constituted in the trajectory of the teacher through the reflections that the act of narrating about the subject to rethink the articulation between theoretical knowledge and practical experiences that it has, determinants for professional development. The analysis technique used was based on the assumption of comprehensive-interpretative analysis (Sousa, 2006 apud Ricouer 1996), which is subdivided into three stages: I - Pre-analysis/Cross-reading; II - Thematic reading/Descriptive analysis units; III - Comprehensive interpretive reading. As a result, it is pointed out that training carries a stigma of being sufficient and having to contemplate what will be experienced in the professional field. However, it is necessary to understand that training does not have this function, because it provides the theoretical knowledge that underlies the practice, and as evidenced in the interviews, part of the disciplines, especially the theoretical, of the course of Pedagogy provide this foundation, evidencing the silence on the subjects of compulsory internship in the course of Pedagogy, for not having been mentioned in the course of the interviews, directing as answer to the problem question " what relationships can be identified from the stage for the constitution of praxis?"is that the training of the interviewees who were affected by the migration of the PPC and also by the passage of the pandemic period, did not provide a relationship for the constitution of pedagogical praxis in the teachers interviewed. Thus, the narratives and the problematization of the experience in school made it possible to glimpse in the academic interviewed the constitution of the theoretical frameworkinitial practical acquired during initial teacher training and which was revisited during its initiation in the teaching profession, however, in its majority, occurred from some theoretical disciplines.